Experimental Study of Wet Cells HHO Generator using Galvanized Steel Plate Electrodes - Putri Pratiwi; Ahmad Fachrurrozi (LP2M - Institut Teknologi Padang, 2020)
Requirements of fuel oil increases along with the increasing their consumption in many sectors such as transportation, industrial and others. This issue has attracted great reseacher’s attention to find the alternative solution as a substitute for fossil fuel energy. Oxygen Hydrogen Hydrogen gas (HHO) can be used as one of this solution. HHO gas can be produced using wet cell HHO generator type. The objective of this research was to construct a simple wet cell HHO generator system and determine the performance of this generator. We use galvanized steel pelate as electrode with thickness 1,2 mm, NaOH catalyst in the electrolyte solution. The results showed that the HHO gas maximum productivity of the cell was 0,0022 L/h, the highest efficiency was 11% with a power consumption of 69.3 Watts.